STUDY OF THE PATHWAY OF FUNCTIONAL DYSPESIA IN PATIENTS WITH TYPE 2 DIABETES (International journal of artificial intelligence, 2025)
This article studies the clinical and pathogenetic features of functional dyspepsia (FD) in patients with type 2 diabetes. During the study, 120 participants were observed, of which 80 were selected as the diabetes group and 40 as the control group. Functional dyspepsia symptoms were assessed based on the Rome IV criteria, and epigastric pain, early satiety, flatulence, and nausea were identified as the most common symptoms. The results showed that the severity of dyspeptic symptoms is directly related to the degree of glucose compensation and HbA1c indicators. Slowing of gastric motility, dysfunction of the autonomic nervous system, and diabetic damage to enteral nerve fibers were shown to be the leading pathogenetic mechanisms in the development of functional dyspepsia. According to the study, it is important to regularly monitor the functioning of the gastrointestinal system in patients with diabetes, identify dyspeptic symptoms early, and take treatment measures based on an individual approach. Such an approach allows improving glycemic control, improving quality of life, and preventing diabetic complications.